Seasonal Influenza Vaccination at a German University Hospital: Distinguishing Barriers Between Occupational Groups - Peschke, Martin; Hagel, Stefan; Rose, Norman; Pletz, Mathias W.; Steiner, Andrea (Frontiers in Medicine, 2022)
The annual influenza vaccination has been officially recommended for medical staff in Germany since 1988. Nevertheless, the vaccination rate among medical staff is still low. The present study deals with the influenza vaccination rate of staff at a German university hospital over time as well as with the reasons that led to a positive vaccination decision and the barriers to acceptance of vaccination. For this purpose, the staff members received questionnaires in which they were asked about influenza vaccination and the reasons for or against vaccination. In addition, the questionnaire contains information on gender, age group, occupational group and presence of a chronic co-morbidity. Logistic regression analysis was used to investigate which of these predictors most strongly influenced the vaccination decision. It was shown that the reasons for or against vaccination differ significantly between the occupational groups and that the occupational group affiliation has the greatest influence on the vaccination decision in the comparison of the investigated predictors. In order to achieve a positive influence on vaccination acceptance, future measures should focus on increasing confidence in vaccination and on increasing the perception of risk from influenza illness. The findings may contribute to future targeted strategies to increase vaccination rates and suggest occupational group-specific interventions.